(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis explores modern methods for early detection, diagnosis, and rehabilitation of congenital and acquired scoliosis in children. Early intervention with comprehensive screening and evidence-based treatments improves outcomes and reduces surgery. Advanced imaging and standardized assessments enhance diagnosis, while personalized rehabilitation, orthotics, and multidisciplinary care optimize spinal function during growth.